Xylem identifies energy efficiency opportunity in wastewater management. Issue 10 (October 2015) - Unknown
Abstract : Increasing energy efficiency through the adoption of readily available wastewater management technologies can slash related emissions by nearly half, according to a study released by Xylem Inc.